2019
DOI: 10.15642/ijet2.2019.8.2.1-7
|View full text |Cite
|
Sign up to set email alerts
|

Five-Option vs Four-Option Multiple-Choice Questions

Abstract: Multiple-choice questions (MCQs) may provide test takers with three, four, or five options and are appreciated for reliability and economic scoring. Five-option MCQs demand much more energy, experience, time, and expertise and may probably be considered to be more difficult four-option and three-option MCQs. Previous studies involved a great number of questions and participants. This study investigated the difference between five-option and four-option MCQs through deletion of non-functioning distracters (NFDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…20 All MCQ related to the present study were five-options. Budiyono (2019) concerned with analysis of non functioning distracters, item facility and item discrimination to compare between 5-options and 4options MCQ, he concluded that teachers are free to choose either the 5-options or 4-options version; depending on the purpose of the test. 21 The present study results revealed that students prefer MCQ with four options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 All MCQ related to the present study were five-options. Budiyono (2019) concerned with analysis of non functioning distracters, item facility and item discrimination to compare between 5-options and 4options MCQ, he concluded that teachers are free to choose either the 5-options or 4-options version; depending on the purpose of the test. 21 The present study results revealed that students prefer MCQ with four options.…”
Section: Discussionmentioning
confidence: 99%
“…Budiyono (2019) concerned with analysis of non functioning distracters, item facility and item discrimination to compare between 5-options and 4options MCQ, he concluded that teachers are free to choose either the 5-options or 4-options version; depending on the purpose of the test. 21 The present study results revealed that students prefer MCQ with four options. So, further studies should be conducted to find out the suitable MCQ format for undergraduate ophthalmology students' assessment.…”
Section: Discussionmentioning
confidence: 99%